2014
DOI: 10.1128/aem.00770-14
|View full text |Cite
|
Sign up to set email alerts
|

Lactulose and Lactobacillus plantarum, a Potential Complementary Synbiotic To Control Postweaning Colibacillosis in Piglets

Abstract: eThe potential of a prebiotic oligosaccharide lactulose, a probiotic strain of Lactobacillus plantarum, or their synbiotic combination to control postweaning colibacillosis in pigs was evaluated using an enterotoxigenic Escherichia coli (ETEC) K88 oral challenge. Seventy-two weanlings were fed four diets: a control diet (CTR), that diet supplemented with L. plantarum (2 ؋ 10 10 CFU · day ؊1 ) (LPN), that diet supplemented with 10 g · kg ؊1 lactulose (LAC), or a combination of the two treatments (SYN). After 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 36 publications
1
67
0
3
Order By: Relevance
“…Major microbiota communities, the dominant phyla, Firmicutes and Bacteroidetes, and two genera, Enterobacteriaceae and Lactobacillus , were assessed by qPCR in pig feces after weaning to achieve a broader view of the bacterial abundance that may potentially be affected differently in H and D groups [55,56]. Post-weaning Bacteroidetes and Enterobacteriaceae abundances were higher in H and D pigs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Major microbiota communities, the dominant phyla, Firmicutes and Bacteroidetes, and two genera, Enterobacteriaceae and Lactobacillus , were assessed by qPCR in pig feces after weaning to achieve a broader view of the bacterial abundance that may potentially be affected differently in H and D groups [55,56]. Post-weaning Bacteroidetes and Enterobacteriaceae abundances were higher in H and D pigs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the number of Escherichia decreased sharply in all treatment groups, most remarkably in the LAC group. Previous reports showed that the lactulose effect was most distinguishable on the population of Escherichia , specifically enterotoxigenic and enteropathogenic E. coli K88 at post‐weaning (Konstantinov et al ., ; Krause et al ., ; Guerra‐Ordaz et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the identified discriminating bacterial genera may have contributions to gut functions in relation to the feed additives with which they are associated. Investigating the influence of probiotic and prebiotic interventions not only in a handful of bacterial groups, which was common in previous studies (Guerra‐Ordaz et al ., ; Zheng et al ., ), but on the total gut microbiota revealed unique bacterial genera that may be beneficial or harmful to pigs; specifically Mitsuokella , Acidaminococcus , Pseudoflavonifractor, Sphaerochaeta , and Anaerovibrio genera were highly influential in the separation of pig groups. The most discriminating bacterium, Mitsuokella , was most abundant in the PRO group (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…enzymes in the intestine, but is metabolized by gut microbiota to short chain fatty acids (SCFAs) in the ileum (Guerra-Ordaz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%